Clinical Comparison of Two Confrontation Naming Measures in Spanish-Speaking People with Epilepsy. (5th October 2021) - Vo, Willa P.; Bailey, K. Chase; Zuverza-Chavarria, Virginia; Nagele, Marielle; Smith, Jason A. D.
Abstract: Objective: Research on the lateralizing value of neuropsychological tests is limited among Latino people with epilepsy (PWE). This study aims to evaluate the utility of two confrontation naming measures in laterality determination. Method: Data were collected from 71 Latino PWE who completed the Vocabulario Sobre Dibujos (VSD) and the Pontón-Satz Modified Boston Naming Test (MBNT). Raw and standardized scores were examined to determine diagnostic accuracy for predicting left hemisphere (LH) epilepsy for the full sample and using a sample-specific median split of educational attainment. Results: The MBNT demonstrated adequate classification accuracy (65.7%, 77.1%) as did the VSD (54.3%, 74.3%) for predicting LH seizure laterality using raw and standardized scores, respectively. For participants with ≥ 9 years of education (HEdu), receiver operator characteristic curve analyses showed a raw/percentile cutoff of ≤ 26/≤ 5 th on the VSD, yielding 53%–58% sensitivity/87%–83% specificity. A raw score cutoff of ≤ 17 on MBNT produced 47% sensitivity/78% specificity for HEdu participants. Conclusions: The VSD was found to have greater flexibility in determining cutoff scores using either raw or standardized scores for predicting seizure laterality. This study provides interpretation guidance, emphasizing education as a pertinent variable, to optimize lateralization accuracy for Latino PWE.